Total synthesis of linear lipodepsipeptide kavaratamide A and its C25-epimer - Sahu, Manas Ranjan; Ingale, Sudhir R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2025)
We report the stereoselective total synthesis of kavaratamide A, a linear lipodepsipeptide from the cyanobacterium Moorena bouillonii (collected in Kavaratti, India), and its unnatural C25-epimer. The convergent approach employs Keck asymmetric allylation to construct the chiral beta-hydroxy carboxylic acid fragment [(3S)-HDA; 3-hydroxydecanoic acid], while the peptide unit was assembled from l-Val, N-Me-l-Ala, (S)-Hiva, and (S)-iPr-O-Me-pyr using well-orchestrated coupling methods to prevent racemization. Modifications to the Keck allylation conditions enabled the synthesis of the C25-epimer with good yield. Cytotoxicity of kavaratamide A and C25-epi-kavaratamide A, assessed using the MTT assay, demonstrated moderate activity against HepG2 and PANC-1 cell lines.